A Case–Control Study to Evaluate Serum Lipoprotein Levels and Other Biomarkers of Cardiovascular Disease in Patients With Psoriasis. Issue 3 (July 2018) - Eleryan, Misty G.; Akhiyat, Sophia; Awosika, Olabola; Wenk, Kurt; Rengifo-Pardo, Monica; Martin, Lisa W.; Ehrlich, Alison
Background: Studies investigating lipid abnormalities associated with psoriasis have reported conflicting results. The purpose of this study is to evaluate differences in serum lipoprotein levels among patients with psoriasis compared to controls via the use of the Vertical Auto Profile (VAP) test, which directly measures the cholesterol concentrations of all 5 lipoprotein classes and their subclasses. We also assess other cardiovascular biomarkers, including highly sensitive C-reactive protein (hs-CRP), lipoprotein-associated phospholipase A2 (Lp-PLA2), and homocysteine. Methods: In this 6-year case–control study, 210 patients (110 patients with psoriasis and 100 controls) elected to participate in VAP testing between November 2009 and April 2016 at The George Washington Medical Faculty Associates dermatology clinic. All psoriatic cases were age-, sex-, and body mass index–matched to control patients. Data were analyzed in June 2016. We evaluated cardiovascular biomarkers in patients with psoriasis versus control patients and whether an association exists between the presence of psoriasis and the level of cardiovascular dysfunction. Results: Compared to the control group, patients with psoriasis had significantly lower high-density lipoprotein (HDL) ( P = .007), HDL2 ( P = .013), and HDL3 cholesterol ( P = .015) as well as higher low-density lipoprotein (LDL) pattern B ( P = .032), LDL3 ( P = .030), and LDL4 cholesterol ( P = .003). Patients with psoriasis also had lower apolipoprotein A1 ( P = .011), lower Lp-PLA2 ( P = .037), and higher hs-CRP ( P = .048). Conclusion: Our findings suggest an increased risk of cardiovascular biomarker dysfunction in patients with psoriasis compared to their matched controls. Serum biomarkers such as high LDL pattern B, LDL3, and LDL4 as well as lower HDL2, HDL3, and total HDL were found to have a higher association with psoriatic disease.